Assessment of Muscle Strength in Para Sport Athletes: A Systematic Review - Qanitah, Talitha; Perdana, Suryo Saputra (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Accurate and reliable muscle strength assessment is essential for monitoring injury risk, monitoring the effectiveness of rehabilitation or strength training programs, and for sport classification purposes. This study aims to look at measurement tools to assess muscle strength in para-athletes, look at the characteristics of muscle strength assessment methods, and determine the validity and reliability of several muscle strength measurement tools. Subjects and Method: This systematic review used methods described in the Cochrane Handbook for Systematic Reviews of Interventions and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data searches in several databases (PubMed, Scopus, and Google Scholar) were conducted using the boolean search method. The keywords used in the literature search were “muscle strength” OR “muscle power” AND “assessment” OR “outcomes” AND “isometric contraction” OR “isotonic contraction” AND “para-sports” OR “para-athletics” AND “paralympic”. Results: Isometric strength testing was shown to be valid and reliable (ICC  0.85) but limited to static measurements; isokinetic testing was shown to be valid and reliable (ICC 0.81-0.95) but required expertise, specialized equipment, and was time-consuming. MMT, although frequently used, shows variable validity and reliability and is highly subjective.Conclusion: Muscle strength assessment with isometric and isokinetic tests is effective for para-athlete classification. However, more standardized muscle strength assessment methods are needed to ensure a more objective classification of para-athletes.